Expanding the Supply and Reducing the Cost of Land for Housing in Urban Areas in Low- and Middle-Income Nations - Satterthwaite, David (Washington, DC: World Bank, 2012)
At the core of the very rapid growth in the number of urban dwellers living in illegal settlements is the gap between the cost or availability of legal land sites on which housing can be built and what most individuals or households can afford to pay for accommodation. For most cities, the problems are further exacerbated by the high spatial concentration of economic activities (and thus employment opportunities). This paper looks at the many ways in which governments can increase the supply and lower the cost of land for housing.